If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2j + -1 = 2 Reorder the terms: -1 + 2j = 2 Solving -1 + 2j = 2 Solving for variable 'j'. Move all terms containing j to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2j = 2 + 1 Combine like terms: -1 + 1 = 0 0 + 2j = 2 + 1 2j = 2 + 1 Combine like terms: 2 + 1 = 3 2j = 3 Divide each side by '2'. j = 1.5 Simplifying j = 1.5
| (3x+1)+(2x+1)+40=180 | | -2x+28= | | 2y+3x(x+1)=y | | 23+3x(x+1)=y | | 72x^5+18x^2= | | f=4(-x)+6 | | 6+ln(x)=4 | | (3)(-6)= | | Ln(x)=3.2958 | | 7n^2+23+6n=0 | | 10(x+2)=7 | | Lnx=3.2958 | | (x+3)x(x-7)=0 | | 15-7=50 | | -36+2w+8w=4 | | 5-9(x+2)-3=5+3(9-3x)-81 | | 2x^2-32x-96=0 | | y=1.1x-1.2 | | g(3x)=(3x)2-4(3x)-10 | | (q-10)*6=16 | | =4x+4 | | 7x-10=10x-18 | | f(x)=6(x)-9 | | -4s+3(2x-5)=31 | | 20-6d=8 | | (3x^3+14x^2+7y-9)+(17x^2+9x+3)= | | 5x-60=3x-8 | | 2x^2-y^3=10 | | 3.5x+y-180=0 | | 9a-4(a-4)=26 | | 8y-9y=44-51 | | 5x(-x^3+2x^2-3x)= |